Evaluating the Roles of Wind‐ and Buoyancy Flux‐Induced Mixing on Phytoplankton Dynamics in the Northern and Central South China Sea. Issue 1 (26th January 2019) - Geng, Bingxu; Xiu, Peng; Shu, Chan; Zhang, Wen‐Zhou; Chai, Fei; Li, Shiyu; Wang, Dongxiao
Abstract: Observations from two Bio‐Argo floats deployed in the northern and central South China Sea (SCS) show distinct seasonal patterns of vertical chlorophyll distribution. There is a permanent subsurface chlorophyll maximum (SCM) located between 60 and 80 m throughout the year and a weak seasonality of surface chlorophyll in the central SCS. In the northern SCS, the SCM shoals to the upper mixed layer in winter and surface phytoplankton shows a clear winter bloom pattern. The mechanism driving the spatial and seasonal differences in phytoplankton dynamics in the euphotic zone remains unclear. Here a coupled physical‐biological model is developed and applied to the northern and central SCS. With model and satellite data, we show that the contrasting patterns in chlorophyll are induced by the spatial variability in winter mixing dynamics. In the northern SCS, the buoyancy flux‐induced mixing plays a dominant role in controlling the seasonal variability of vertical nutrient transport and phytoplankton production, which leads to the peak of surface chlorophyll and the significant shoaling of the SCM in winter. In the central SCS, the intensity of the buoyancy flux is reduced and both buoyancy flux‐ and wind‐induced mixing control the winter mixing dynamics. However, the combination of these two mixing processes is weaker than in the northern SCS and the vertical nutrient transport is limited to the layer above the SCM, resulting in the reduced seasonality of surface chlorophyll and the relatively stable SCM all year round in the central SCS. Plain Language Summary: Both satellite and Bio‐Argo floats show a significant increase of surface chlorophyll concentration in winter in the northern South China Sea (SCS) but a very weak seasonal change in the central SCS. We used a coupled physical‐biological model to systematically study the mechanism driving these spatial and seasonal differences. The model can reasonably simulate the different chlorophyll distribution patterns identified by observations. We found that the buoyancy flux‐induced mixing plays a dominant role in controlling the seasonal change of chlorophyll in the northern SCS. In the central SCS, both buoyancy flux‐ and wind‐induced mixing control the winter mixing dynamics. However, the combination of these two mixing dynamics is not as strong as that in the northern SCS and the vertical nutrient transport is only limited to the layer above the SCM, resulting in the reduced seasonality of surface chlorophyll and the relatively stable SCM all year round in the central SCS. Key Points: There is a stable SCM and a weak seasonality of surface CHL in the central SCS, while there is a shoaling SCM and a clear winter bloom in the north In the northern SCS, buoyancy flux‐induced mixing plays a dominant role in controlling winter mixing and seasonal phytoplankton dynamics In the central SCS, both buoyancy flux‐ and wind‐induced mixing control the winter mixing